Role of cyclooxygenase-2 in intestinal injury in neonatal rats - LU, HUI (D.A. Spandidos, 2014)
Necrotizing enterocolitis (NEC) is the most common gastrointestinal emergency in premature neonates. The pathogenesis of NEC remains poorly understood. The present study aimed to investigate the dynamic change and role of cyclooxygenase-2 (COX-2) in neonatal rats with intestinal injury. Wistar rats, <24 h in age, received an intraperitoneal injection with 5 mg/kg lipopolysaccharide (LPS). Ileal tissues were collected at 1, 3, 6, 12 and 24 h following the LPS challenge for histological evaluation of NEC and for measurements of COX-2 mRNA. The correlation between the degree of intestinal injury and expression of COX-2 mRNA was determined. The LPS-injected pups showed a significant increase in injury scores compared to the control, and the most deteriorating change was at 12 h. COX-2 mRNA expression was upregulated following LPS injection. There was a significantly positive correlation between COX-2 mRNA and the grade of intestinal injury within 12 h, whereas COX-2 mRNA expression had a significantly negative correlation with the severity of intestinal injury at 24 h. COX-2 plays an important role in LPS-induced intestinal injury and the repair processes. Caution should be exerted concerning the potential therapeutic uses of COX-2 inhibitors or promoters in NEC.